Assessment of the antimicrobial activity of Casearia sylvestris extract against oral pathogenic microorganisms - W.L.F. Tavares; A.C.M. Apolônio; R.T. Gomes; K.I.R. Teixeira; M.G.L. Brandão; V.R. Santos (São Paulo State University (UNESP), 2008)
An ethanolic extract of leaves from the tree Casearia sylvestris, known as guaçatonga in Brazil, was tested for in vitro activity against oral pathogenic bacteria and fungi. The results showed susceptibility of all the microorganisms tested. This study suggests a potential use of ethanolic extract of C. sylvestris as a novel treatment of oral infectious conditions, such as denture stomatitis, periodontitis and dental caries.